Saatnya Menengok ke Barat: Sebuah Interpretasi Baru Tentang Distribusi Temuan Homo Erectus di Jawa - Harry Widianto; Sofwan Noerwidi (Balai Arkeologi Yogyakarta, 2020)
Paleontological data indicate that the beginning of Java Island’s occupation occurred at the Plio-Pleistocene boundary, around 2.4 Mya. However, the oldest Homo erectus fossil was found in Sangiran, around 1.5 Mya. Recently, Pleistocene sites were discovered from the western part of Java, e.g. Rancah, Semedo, and Bumiayu. This paper describes the significance of archeological, paleontological, and especially paleoanthropological data from the new sites, and their implications to the future Quaternary prehistory research strategies determination. Data collection methods include literature study and surveys, while analysis is carried out on the geological, archeological, paleontological, and paleoanthropological data. The result shows the dispersal of Homo erectus is extended to the western part of Java, between 1.8-1.7 Mya, older than the oldest Homo erectus of Sangiran. A new window of the human arrival on this island is identified. So, it is time to look to the west, and intensive research should be carried out to those areas.